2020
DOI: 10.36834/cmej.56940
|View full text |Cite
|
Sign up to set email alerts
|

International health experiences in postgraduate medical education: A meta-analysis of their effect on graduates’ clinical practice among underserved populations

Abstract: Background: International health experiences (IHEs) are popular among medical learners and provide a valuable learning experience. IHE participants have demonstrated an increased intention to care for underserved populations in the future, but what is its actual impact on practice? This study evaluates the effect of postgraduate IHE participation on the future careers of clinicians regarding their work among underserved populations. Methods: We conducted a systematic review and meta-analysis of peer-revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The findings of this study suggest that policymakers should prioritize and allocate extra resources to quality postgraduate training across the country and develop motivational and support strategies for enticing medical graduates to pursue diverse specialties and subspecialties. Our findings reveal that the emigration intentions of Afghan medical students (51.3%) correspond to those of medical students from other developing countries [14,17,19]. Advanced and quality medical education and yearning for a decent personal life were the most frequent motives influencing the respondent's emigration intentions.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The findings of this study suggest that policymakers should prioritize and allocate extra resources to quality postgraduate training across the country and develop motivational and support strategies for enticing medical graduates to pursue diverse specialties and subspecialties. Our findings reveal that the emigration intentions of Afghan medical students (51.3%) correspond to those of medical students from other developing countries [14,17,19]. Advanced and quality medical education and yearning for a decent personal life were the most frequent motives influencing the respondent's emigration intentions.…”
Section: Discussionmentioning
confidence: 57%
“…Finally, leaving your comfort zone and living in a socio-culturally different environment is a pretty enriching and globally favored life experience. Studies have shown that postgraduate training enrollment influences students' decisions concerning permanent residency in their host country [14][15][16][17][18][19]. Internal medicine and surgery were typical career choices reported by medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation